Epigenetic Biomarkers: Potential Applications in Gastrointestinal Cancers. (6th March 2014) - Li, Jiaqiu; Jin, Hongchuan; Wang, Xian
Abstract : Genetics and epigenetics coregulate the cancer initiation and progression. Epigenetic mechanisms include DNA methylation, histone modification, chromatin remodeling, and noncoding RNAs. Aberrant epigenetic modifications play a fundamental role in the formation of gastrointestinal cancers. Advances in epigenetics offer a better understanding of the carcinogenesis and provide new insights into the discovery of biomarkers for diagnosis, and prognosis prediction of human cancers. This review aims to overview the epigenetic aberrance and the clinical applications as biomarkers in gastrointestinal cancers mainly gastric cancer and colorectal cancer.